Seasonality, capital inflexibility, and the industrialization of animal production - Jutta Roosen; David A. Hennessy (Kiel University, Department of Food Economics and Consumption Studies, 2004)
Among prominent recognized features of the industrialization of animal production over the past half century are growth in the stock of inflexible, or use-dedicated capital, as an input in production, and growth in productivity. Less recognized is a trend toward aseasonal production. We record the deseasonalization of animal production in the US and European countries over the past 70 years. We also suggest that A) lower seasonality can precede or Granger-cause increased productivity due to increased capital intensity, and B) productivity improvements can Granger-cause lower seasonality. Process A) should be more likely earlier in the industrialization process. For US dairy production, our empirical tests find some evidence that process A) operated early in the 20th Century while process B) operated in more recent times.
Keywords: 330; Capital Intensity; Causality; Dairy; Regional Production Systems; Tierhaltung; Saisonschwankung; Kapitalintensität; Kausalanalyse; Schätzung; Milchviehhaltung; USA